2020
DOI: 10.1002/jmri.27283
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Biparametric and Multiparametric MRI for Clinically Significant Prostate Cancer Detection With PI‐RADS Version 2.1

Abstract: Background: Biparametric MRI (bpMRI) without dynamic contrast-enhanced MRI (DCE-MRI) results in an elimination of adverse events, shortened examination time, and reduced costs, compared to multiparametric MRI (mpMRI). The ability of bpMRI to detect clinically significant prostate cancer (csPC) with the Prostate Imaging and Reporting Data System version 2.1 (PI-RADS v2.1) compared to standard mpMRI has not been studied extensively. Purpose: To compare the interobserver reliability and diagnostic performance for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 28 publications
3
74
0
1
Order By: Relevance
“…Nine studies were retrospective, [10][11][12]15,[22][23][24][25][26] and one study was prospective. 13 Five studies made evaluations on a per-lesion basis, 10,11,13,22,25 and five studies made them on a per-patient basis. 12,15,23,24,26 MRI was performed using 3-T scanners in nine studies 10-13,15,23-26 and using 1.5-T scanners in one study.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine studies were retrospective, [10][11][12]15,[22][23][24][25][26] and one study was prospective. 13 Five studies made evaluations on a per-lesion basis, 10,11,13,22,25 and five studies made them on a per-patient basis. 12,15,23,24,26 MRI was performed using 3-T scanners in nine studies 10-13,15,23-26 and using 1.5-T scanners in one study.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…one study, 26 and either targeted biopsy and systematic biopsy or radical prostatectomy in one study. 25…”
Section: Notementioning
confidence: 99%
See 1 more Smart Citation
“…In a Japanese cohort, the e cacy of mpMRI and bpMRI for detecting sPC as a triage test was also reported [25][26][27]. However, no multivariate risk prediction models for detecting sPC based on PI-RADS scores of mpMRI or bpMRI as ordinal variables among Japanese populations have been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…Also DCE-MRI with gadolinium chelate increases the burden on patients in terms of examination time, cost, and them potentially developing nephrogenic systemic fibrosis. A study showed that the diagnostic performance of biparametric MRI (bpMRI), which is an abbreviated prostate MRI protocol without DCE-MRI, was comparable to that of mpMRI [4]. Prostate MRI assessment relies on human experts, specialized training, and experience [5] with considerable inter-reader variability.…”
Section: Introductionmentioning
confidence: 99%